Pemikiran Ekonomi Islam Umar bin Khattab dan Relevansinya terhadap Kebijakan Ekonomi Kontemporer - Fajri Rozikin; Mumhammad Daffa Pratama (Indo Publishing, 2026)
Islamic economic thought plays an important role in shaping an economic system based on the values of justice, balance, and social welfare. In Islamic history, the period of the Khulafā’ al-Rāshidīn represents the early formation of economic policies derived from Islamic principles, particularly during the leadership of Umar ibn Khattab. Umar ibn Khattab is widely recognized as a leader who placed great emphasis on state economic management and public welfare. This study aims to analyze the Islamic economic thought of Umar ibn Khattab and its relevance to contemporary economic policies. The research employs a qualitative method with a library research approach through the examination of classical and contemporary literature. The findings indicate that Umar ibn Khattab’s economic thought encompasses transparent and accountable management of the baitul mal, equitable fiscal policies, protection of vulnerable groups, and the active role of the state in maintaining market stability and justice. These principles are in line with the objectives of Islamic law (maqāṣid al-sharī‘ah) and demonstrate strong relevance in addressing modern economic policy challenges, particularly in achieving social justice, equitable wealth distribution, and sustainable economic development.